ONLINE LEARNING AMIDST COVID-19 PANDEMIC: SECONDARY SCHOOL STUDENTS’ PERCEPTIONS TOWARD CHALLENGES AND NEEDED MATERIALS - Ivan Ivan Nurseha (Graduate Program, University of Islam Malang, 2021)
AbstractThis research focused on students’ perception toward challenges and needed materials. The researcher used a descriptive qualitative research as design method because it was comparable to collect the data from students’ perception and gave interview to collect the data. The data was collected from the secondary school students of MA Mambaus Sholihin Suci Manyar Gresik which have been learned using online learning. The sample had been 10 students chosen through purposive sampling which snowball sampling approach. The students selected to be a representative sample of the population have met the criteria specified by researcher. The findings of the research showed that mostly the students gave good perception about online learning. They were improving their learning and got a new experience of the new media applied by teacher in online learning. On the other hand, some students gave perception that online learning has obstacles that bad network, the quality of mobile phone of the student itself and the capacity of the application used in online learning. It can be concluded that online learning to be an effective learning resource when supported by adequate infrastructure such as good networks. Then online learning can motivate students to improve their knowledge, skills and generate new experiences for students.Keywords: Students’ perception, Online Learning, Challenges and Needs.